The Effect of Connected “Smart” Inhalers on Medication Adherence - Zabczyk, Caroline; Blakey, John D. (Frontiers in Medical Technology, 2021)
Asthma and COPD are highly prevalent worldwide, and major sources of morbidity. Key barriers to reducing harm from these conditions are the widespread and related issues of low use of prescribed inhaled therapy, use of medicines differently from that prescribed, suboptimal inhaler technique, and lack of adherence to action plans. Connected smart inhalers show great potential to improve these domains and thus outcomes from airways disease. In this mini-review, we considered the published evidence that the use of smart inhalers leads to more doses of preventative treatment being taken on time and with appropriate technique. We found multiple trials across a variety of settings and age groups showing that smart inhaler use with their audio-visual reminders and potential for healthcare professional feedback substantially improves the number of doses of preventative treatment taken. Trial evidence also supports the use of feedback from smart inhalers in improving true concordance (doses taken correctly and on time), though only for a single type of smart device. The relative lack of study data is in contrast with the potential impact of smart inhalers. Major research questions remain unresolved, as do issues of who might fund future large scale studies, how they may be considered by guideline committees, and how to implement effective solutions.